Microporous-mesoporous composite molecular sieve, preparation method thereof and application of microporous-mesoporous composite molecular sieve in reaction for preparing low-carbon olefin through direct catalytic cracking of waste plastics
By using microporous-mesoporous composite molecular sieve as a catalyst, the problem of low-carbon olefin content in waste plastics in the prior art is solved, and the efficient conversion of waste plastics into low-carbon olefins is achieved, and the quality and economic benefits of the product are improved.
Patent Information
- Application Number
- CN202311308571.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-10-10
AI Technical Summary
In the prior art, the content of low-carbon olefins recovered in chemical recycling and utilization of waste plastics is relatively small, making it difficult to effectively produce pure and high-quality low-carbon olefins.
Microporous-mesoporous composite molecular sieve was used as catalyst, and the microporous-mesoporous composite molecular sieve with uniform pore distribution was prepared by mixing ZSM-23 molecular sieve with two-dimensional hexagonal all-silicon mesoporous molecular sieve and ball milling and calcining. Low-carbon olefins were prepared for direct catalytic cracking of waste plastics.
The efficient conversion of waste plastics into low-carbon olefins is achieved, the selectivity and yield of low-carbon olefins are improved, and the economic benefits are good, and the process conditions are mild and easy to operate.
Smart Images

Figure CN119797389A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalysts and polymer material recycling, and in particular to a microporous-mesoporous composite molecular sieve and a preparation method thereof, as well as an application in the direct catalytic cracking of waste plastics to produce light olefins. Background Art
[0002] Since the advent of plastic products in the 20th century, they have been widely used in various fields around the world with the characteristics of light weight, high strength, corrosion resistance, good chemical stability, easy processing, and beautiful and practical. However, plastics are difficult to degrade naturally. Although conventional landfill technology requires little investment and is simple to operate, it will occupy a large amount of land and cause land pollution. Although incineration technology can achieve the reduction requirements and recover some energy at the same time, this process is prone to release a large amount of hydrocarbons, nitrides, sulfides and highly toxic substances, which directly threaten human and ecological health. Therefore, the recycling and high-value utilization of waste plastics as a measure to save energy and protect the environment has been widely valued by countries around the world. The methods for recycling and utilizing waste plastics mainly include classified recycling, preparation of monomer raw materials, production of clean fuel and use for power generation.
[0003] my country's plastics industry is one of the pillar industries of the national economy. At present, my country has entered the ranks of the world's major plastics countries. Under the policy background of the new plastic restriction order, the sharp decline in imports, and garbage classification, my country's waste plastic recycling companies are gradually getting rid of the old path of extensive expansion in the past, and gradually examining the industrial layout with the perspective of green development. Continue to deepen cooperation with environmental protection and sanitation companies to gradually achieve the goal of green, low-carbon and circular development. Large-scale waste plastic recycling companies with standardized operations will gradually further refine the recycled waste plastics, continue to develop and apply new technologies and new products for waste plastics, gradually expand the application field of waste plastics, and increase the added value of recycled plastic products. In the existing technology, the chemical recycling scheme for waste plastics is mainly waste plastic cracking technology. There are three basic methods for waste plastic cracking, namely: thermal cracking (one-stage method), catalytic cracking (one-stage method) and thermal cracking-catalytic modification (two-stage method). The earliest developed waste plastic cracking technology is thermal cracking technology. This technology refers to a thermal conversion process in which a thermochemical decomposition reaction occurs under high temperature and anaerobic conditions to convert large molecular weight organic matter in waste plastic products into small molecular weight liquids, fuel gas, coke and other substances. The reaction temperature of this process is generally controlled at 350-900°C. If a catalyst is added during the thermal cracking process, it is a catalytic thermal cracking technology, which can not only reduce the cracking temperature, but also improve product performance. The thermal cracking-catalytic reforming method is an improvement on the catalytic cracking method. After the waste plastics are thermally cracked, a catalyst is used to catalytically reform the cracking gas. This method has higher product quality, more flexible operation and lower operating costs than the thermal cracking method and the catalytic cracking method, but the process is more complicated.
[0004] Cracking technology has wide flexibility in treating waste plastics and good energy recovery, and is one of the waste plastic treatment technologies with broad application prospects. In the prior art, the products produced by the one-step thermal cracking method and the one-step catalytic cracking method are mainly fuel oil, and only a small amount of low-carbon olefins (ethylene, propylene, butene) can be obtained. If a large amount of low-carbon olefins are required, a two-stage method of thermal cracking-catalytic modification is required. Therefore, exploring a new chemical recovery process to produce pure and high-quality final products is an important research direction for plastic waste treatment. Summary of the invention
[0005] The purpose of the present invention is to provide a microporous-mesoporous composite molecular sieve and its preparation method and its application in the direct catalytic cracking of waste plastics to produce light olefins in order to solve the problem of low content of light olefins recovered in the current chemical recycling of waste plastics. The use of the new catalyst of the present invention not only solves the problem of recycling waste plastics, but also increases the production of light olefins, an important chemical raw material.
[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a microporous-mesoporous composite molecular sieve, wherein the microporous-mesoporous composite molecular sieve comprises a ZSM-23 molecular sieve and a two-dimensional hexagonal all-silicon mesoporous molecular sieve, wherein the specific surface area of the two-dimensional hexagonal all-silicon mesoporous molecular sieve is 500-800m 2 / g, the pore volume is 0.8-1.5mL / g, and the average pore diameter is 6-9nm; and based on the total weight of the microporous-mesoporous composite molecular sieve, the content of the ZSM-23 molecular sieve is 40-80% by weight, and the content of the two-dimensional hexagonal all-silica mesoporous molecular sieve is 20-60% by weight.
[0007] The second aspect of the present invention provides a method for preparing the aforementioned microporous-mesoporous composite molecular sieve, wherein the preparation method comprises:
[0008] (1) hydrolyzing a template, a silicon source and an acidic aqueous solution under hydrolysis gel-making conditions to obtain a gel mixture; crystallizing the gel mixture; and filtering and first drying the product obtained by the crystallization to obtain a mesoporous molecular sieve raw powder;
[0009] (2) The mesoporous molecular sieve raw powder is mixed with ZSM-23 molecular sieve and subjected to ball milling treatment, and the solid powder obtained after ball milling is subjected to a second drying and calcining treatment to obtain a microporous-mesoporous composite molecular sieve.
[0010] The third aspect of the present invention provides an application of the aforementioned microporous-mesoporous composite molecular sieve in the direct catalytic cracking of waste plastics to produce low-carbon olefins, wherein the application comprises: contacting the powder of the waste plastics with a catalyst for reaction, and the catalyst is the aforementioned microporous-mesoporous composite molecular sieve.
[0011] Through the above technical solution, the technical solution of the present invention has the following advantages:
[0012] 1. The microporous-mesoporous composite molecular sieve provided by the present invention includes a ZSM-23 microporous molecular sieve with an appropriate amount of acid centers on the surface and a two-dimensional hexagonal all-silicon mesoporous molecular sieve with a larger pore size. It has a stable structure and good high temperature resistance, and is conducive to the diffusion of raw material and product molecules during the cracking reaction.
[0013] 2. In the preparation process of the microporous-mesoporous composite molecular sieve provided by the present invention, the ZSM-23 molecular sieve and the two-dimensional hexagonal all-silicon mesoporous molecular sieve raw powder are mixed and ball-milled and calcined, and the microporous channels and mesoporous channels in the obtained microporous-mesoporous composite molecular sieve are evenly distributed.
[0014] 3. The microporous-mesoporous composite molecular sieve provided by the present invention can convert waste plastics into low-carbon olefins in one step when used for direct catalytic cracking of waste plastics to produce low-carbon olefins, which is a new method for chemical recycling of waste plastics. It not only solves the problem of recycling waste plastics, but also increases the production of important chemical raw materials, low-carbon olefins, and has good economic benefits.
[0015] 4. When the microporous-mesoporous composite molecular sieve provided by the present invention is used for direct catalytic cracking of waste plastics to produce light olefins, the process conditions are mild, the operation is easy, and the requirements for the reaction device are not high.
[0016] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:
[0018] Figure 1 is a wide-angle X-ray diffraction (XRD) spectrum of the ZSM-23 molecular sieve molecular sieve A prepared in Example 1 of the present invention;
[0019] Figure 2 is a small-angle X-ray diffraction (XRD) spectrum of the microporous-mesoporous composite molecular sieve A prepared in Example 1 of the present invention;
[0020] Figure 3 This is a pore size distribution diagram of the microporous-mesoporous composite molecular sieve A prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0021] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0022] As mentioned above, the first aspect of the present invention provides a microporous-mesoporous composite molecular sieve, wherein the microporous-mesoporous composite molecular sieve comprises a ZSM-23 molecular sieve and a two-dimensional hexagonal all-silicon mesoporous molecular sieve, wherein the specific surface area of the two-dimensional hexagonal all-silicon mesoporous molecular sieve is 500-800m 2 / g, the pore volume is 0.8-1.5mL / g, and the average pore diameter is 6-9nm; and based on the total weight of the microporous-mesoporous composite molecular sieve, the content of the ZSM-23 molecular sieve is 40-80% by weight, and the content of the two-dimensional hexagonal all-silica mesoporous molecular sieve is 20-60% by weight.
[0023] The inventor of the present invention has found that in the prior art, there is no process for directly catalytically cracking waste plastics to produce low-carbon olefins (including ethylene, propylene, and butene). The purpose of the present invention is to solve this problem. According to the inventor's understanding of the physical and chemical properties of multiphase catalysts, the catalyst used for catalytic cracking of waste plastics to directly prepare low-carbon olefins should have a certain acidity. In addition, the catalyst for catalytic cracking of waste plastics needs to have good thermal stability. ZSM-23 molecular sieve not only has acidity of appropriate strength, but also has good thermal stability (the crystal phase can still remain stable after high-temperature roasting at 650°C), and is a more suitable catalyst for catalytic cracking of waste plastics. However, ZSM-23 molecular sieve has an MTT topological structure, a one-dimensional pore composed of ten-membered rings, and a pore size of only 0.56nm×0.45nm. In view of the fact that ZSM-23 is a microporous molecular sieve with a small pore size, the improvement of the catalytic performance of ZSM-23 molecular sieve is seriously limited. The molecular weight of waste plastic products is large and the molecular chain is relatively long. In the cracking reaction of waste plastic products, it is difficult for the larger reactant molecules and product molecules to diffuse in the narrow channels, which not only affects the contact between the reactants and the active centers, but also easily leads to the occurrence of side reactions such as deep dehydrogenation, which in turn leads to the decline of catalyst performance. Compared with microporous molecular sieves, two-dimensional hexagonal all-silica mesoporous molecular sieve materials have larger pore sizes (pore diameters between 6-9nm) and larger pore volumes (up to 0.8cm 3 / g or more), which is very suitable for catalytic reactions involving macromolecules. However, the two-dimensional hexagonal all-silicon mesoporous molecular sieve is an all-silicon material, and only contains a small amount of silanol on the surface, and the acidity is extremely weak, which is not suitable for being used alone as a catalyst to catalyze the cracking reaction of waste plastics. The inventors of the present invention found in the development and research of waste plastic cracking catalysts that if the structural advantages of all-silicon mesoporous inorganic materials and the surface acidic centers of microporous molecular sieves are comprehensively utilized, and a certain amount of two-dimensional hexagonal all-silicon mesoporous molecular sieves are mixed with ZSM-23 molecular sieves, the specific surface area and pore volume of the catalyst can be effectively increased, and the internal diffusion performance in the reaction can be significantly improved. When used as a cracking catalyst in the catalytic conversion reaction of waste plastics, it can not only effectively improve the activity of the cracking catalyst, but also increase the selectivity of light olefins.
[0024] According to the present invention, preferably, based on the total weight of the microporous-mesoporous composite molecular sieve, the content of the ZSM-23 molecular sieve is 50-70% by weight, and the content of the two-dimensional hexagonal all-silicon mesoporous molecular sieve is 30-50% by weight; more preferably, based on the total weight of the microporous-mesoporous composite molecular sieve, the content of the ZSM-23 molecular sieve is 55-65% by weight, and the content of the two-dimensional hexagonal all-silicon mesoporous molecular sieve is 35-45% by weight. In the present invention, the use of the aforementioned specific content of each component can make the prepared microporous-mesoporous composite molecular sieve have better catalytic activity and higher selectivity for light olefins when used for direct catalytic cracking of waste plastics to prepare light olefins.
[0025] According to the present invention, the specific surface area of the microporous-mesoporous composite molecular sieve is 290-440m 2 / g, pore volume is 0.8-1mL / g, pore size distribution is bimodal, and the most probable pore sizes corresponding to the bimodal distribution are 0.4-0.7nm and 5-10nm respectively; preferably, the specific surface area of the microporous-mesoporous composite molecular sieve is 320-400m 2 / g, pore volume is 0.85-0.93mL / g, pore size distribution is bimodal, and the most probable pore sizes corresponding to the bimodal distribution are 0.5-0.6nm and 6-9nm respectively; more preferably, the specific surface area of the microporous-mesoporous composite molecular sieve is 337-380m 2 / g, pore volume is 0.86-0.9mL / g, pore size distribution is bimodal, and the most probable pore sizes corresponding to the bimodal distribution are 0.5-0.6nm and 7-8nm, respectively. In the present invention, when the microporous-mesoporous composite molecular sieve has the aforementioned specific structural parameters, it can be used for direct catalytic cracking of waste plastics to prepare light olefins with better catalytic activity and higher light olefin selectivity.
[0026] According to the present invention, the SiO 2 / Al 2 O 3 The molar ratio may be 90-130, preferably 100-120.
[0027] According to the present invention, the ZSM-23 molecular sieve can be purchased commercially or prepared in a laboratory. In the present invention, the ZSM-23 molecular sieve can be prepared by the following method:
[0028] At room temperature, dimethylamine and aluminum sulfate were dissolved in a certain amount of distilled water to prepare solution A; silica sol was mixed with an aqueous solution of alkali to prepare solution B. Solution A was slowly added to solution B and stirred for 5 hours to obtain a gel mixture; the gel mixture was crystallized and then filtered, washed, dried and calcined to obtain ZSM-23 molecular sieve.
[0029] According to the present invention, in the method for preparing ZSM-23 molecular sieve, the base is preferably sodium hydroxide or potassium hydroxide.
[0030] According to the present invention, the preparation method of ZSM-23 molecular sieve, the aluminum sulfate, dimethylamine, silica sol (in the form of SiO 2 ), alkali (in OH - The molar ratio of argon (calculated) to water is 1: (55-100): (90-130): (8-16): (2500-4500), preferably 1: (65-85): (100-120): (10-14): (3000-4000).
[0031] According to the present invention, the preparation method of ZSM-23 molecular sieve, the crystallization process can be carried out in a hydrothermal reactor equipped with a polytetrafluoroethylene liner, and the crystallization conditions are: crystallization temperature 140-180°C, crystallization time 24-72h; preferably, the temperature is 150-170°C, and the time is 40-60h. Preferably, in order to achieve a better crystallization effect, rapid stirring is required during the crystallization process.
[0032] According to the present invention, the preparation method of ZSM-23 molecular sieve, the washing conditions are not particularly limited, for example, the washing process may include: obtaining a solid product after filtration, repeatedly washing the solid product with distilled water (the number of washing times can be 2-10) and then filtering.
[0033] According to the present invention, in the method for preparing ZSM-23 molecular sieve, the drying conditions may be: drying temperature 60-150° C., drying time 3-20 h; preferably, the temperature is 80-130° C., and the time is 5-16 h.
[0034] According to the present invention, in the method for preparing ZSM-23 molecular sieve, the calcination conditions may be: calcination temperature 450-650° C., calcination time 5-30 h; preferably, the temperature is 500-600° C., and the time is 8-20 h.
[0035] The second aspect of the present invention provides a method for preparing the aforementioned microporous-mesoporous composite molecular sieve, wherein the preparation method comprises:
[0036] (1) hydrolyzing a template, a silicon source and an acidic aqueous solution under hydrolysis gel-making conditions to obtain a gel mixture; crystallizing the gel mixture; and filtering and first drying the product obtained by the crystallization to obtain a mesoporous molecular sieve raw powder;
[0037] (2) The mesoporous molecular sieve raw powder is mixed with ZSM-23 molecular sieve and subjected to ball milling treatment, and the solid powder obtained after ball milling is subjected to a second drying and calcining treatment to obtain a microporous-mesoporous composite molecular sieve.
[0038] The inventors of the present invention have found that mixing a certain amount of two-dimensional hexagonal all-silicon mesoporous molecular sieve with ZSM-23 molecular sieve can effectively increase the specific surface area and pore volume of the catalyst and significantly improve the internal diffusion performance in the reaction. However, if the two prepared molecular sieves are mechanically mixed, the microporous channels and mesoporous channels in the obtained mixed molecular sieve are unevenly distributed, and the effect of improving the diffusion performance is not significant enough. In the present invention, the inventors mixed the mesoporous molecular sieve raw powder (two-dimensional hexagonal all-silicon mesoporous molecular sieve raw powder) with the ZSM-23 molecular sieve and then calcined it by ball milling to obtain a microporous-mesoporous composite molecular sieve. The composite molecular sieve obtained by this method has a uniform distribution of microporous channels and mesoporous channels, and has high catalytic activity and high selectivity for light olefins when used for catalytic cracking reactions of waste plastics.
[0039] According to the present invention, in step (1), the template is a nonionic surfactant, preferably low, and the general formula of the template is EO a PO b EO a The polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer is preferably P123 (EO 20 PO 70 EO 20 ).
[0040] According to the present invention, in step (1), the silicon source is an organic silicate or an inorganic silicon source, preferably one or more of methyl orthosilicate, ethyl orthosilicate, water glass and sodium metasilicate.
[0041] According to the present invention, in step (1), the acidic aqueous solution is one or more of hydrochloric acid, sulfuric acid aqueous solution and nitric acid aqueous solution, preferably hydrochloric acid aqueous solution; the molar concentration of the solute in the acidic aqueous solution is 0.5-3 mol / L, preferably 1-2 mol / L.
[0042] According to the present invention, in step (1), the molar ratio of the template, the silicon source, the acid in the acidic aqueous solution and the water in the acidic aqueous solution is 1:(40-100):(120-400):(6000-10000), preferably 1:(50-80):(150-300):(7000-9500).
[0043] According to the present invention, in step (1), the conditions for hydrolysis and gelling include: temperature of 20-60°C, preferably 30-50°C; time of 12-36h, preferably 18-30h.
[0044] According to the present invention, in step (1), the crystallization conditions include: a crystallization temperature of 70-150° C., preferably 80-120° C.; a crystallization time of 8-72 hours, preferably 20-30 hours. It is well known to those skilled in the art that the crystallization is generally carried out in a hydrothermal autoclave, which will not be described in detail here.
[0045] According to the present invention, in step (1), there are no special requirements for the filtration process, and it can be a filtration method known in the art, including gravity filtration, pressure filtration, vacuum filtration or centrifugal filtration. Preferably, the filtration process specifically includes: using a suction bottle, vacuuming the bottom side of the funnel or filtering using a centrifugal filter.
[0046] According to the present invention, in step (1), the first drying temperature is 70-120° C. and the time is 3-10 h.
[0047] According to the present invention, in step (2), the weight ratio of the mesoporous molecular sieve raw powder to the ZSM-23 molecular sieve is 1:(0.3-5), preferably 1:(0.5-3).
[0048] According to the present invention, in step (2), the ball milling is carried out in a ball mill, wherein the diameter of the grinding balls in the ball mill can be 2-3 mm; the number of grinding balls can be reasonably selected according to the size of the ball mill jar, and for a ball mill jar of 100-300 mL, 2-8 grinding balls can usually be used; the material of the grinding balls is agate or polytetrafluoroethylene, preferably agate. The conditions of the ball milling include: the rotation speed of the grinding balls can be 200-600 r / min, preferably 300-500 r / min; the temperature in the ball mill jar can be 30-90°C, preferably 40-80°C; the ball milling time can be 5-50h, preferably 8-24h.
[0049] According to the present invention, in step (2), the second drying temperature is 70-150° C. and the time is 3-20 hours.
[0050] According to the present invention, in step (2), the calcination conditions include: a calcination temperature of 450-650° C., preferably 500-600° C.; and a calcination time of 5-30 h, preferably 8-20 h.
[0051] The third aspect of the present invention provides an application of the aforementioned microporous-mesoporous composite molecular sieve in the direct catalytic cracking of waste plastics to produce low-carbon olefins, wherein the application comprises: contacting the powder of the waste plastics with a catalyst for reaction, and the catalyst is the aforementioned microporous-mesoporous composite molecular sieve.
[0052] In the present invention, the conditions for contacting the waste plastic powder with the microporous-mesoporous composite molecular sieve include: the contact temperature can be 420-580°C, preferably 450-540°C; the contact pressure can be 0.01-3MPa, preferably 0.01-1Mpa, more preferably 0.05-0.5Mpa; the contact time can be 0.5-12h, preferably 1-5h; the weight ratio of the microporous-mesoporous composite molecular sieve to the waste plastic powder can be 1:(0.5-50), preferably 1:(2-30).
[0053] The present invention will be described in detail below through examples.
[0054] In the following examples and comparative examples:
[0055] The small-angle XRD test of the sample was carried out on a D8 ADVANCE high-power rotating target X-ray diffractometer produced by BRUKER AXS of Germany, with a scanning range of 0.5-10°.
[0056] The wide-angle XRD test of the sample was carried out on an X'Pert MPD X-ray powder diffractometer of Philips Company in the Netherlands, with a Cu Kα target and a scanning range of 2θ=5-90°.
[0057] The pore structure parameter analysis of the samples was carried out on an ASAP2020-M+C adsorption instrument purchased from Micromeritics, Inc., USA. The samples were vacuum degassed at 350°C for 4 hours before measurement, and the specific surface area of the samples was calculated using the BET method, and the pore volume was calculated using the BJH model.
[0058] The elemental analysis experiment of the samples was carried out on an EagleⅢ energy dispersive X-ray fluorescence spectrometer produced by EDAX, USA.
[0059] The drying oven was produced by Shanghai Yiheng Scientific Instrument Co., Ltd., model DHG-9030A.
[0060] The muffle furnace is produced by CARBOLITE, model CWF1100.
[0061] The P123 used in the examples and comparative examples was purchased from Aldrich, and the other reagents used in the examples and comparative examples were purchased from Sinopharm Chemical Reagent Co., Ltd., and the purity of the reagents was analytical grade.
[0062] Example 1
[0063] (1) Preparation of ZSM-23 molecular sieve
[0064] At room temperature, dimethylamine and aluminum sulfate were dissolved in distilled water and stirred for 24 hours to prepare a clear solution A; silica sol was mixed with an aqueous solution of sodium hydroxide to prepare a mixed solution B. 2 The molar ratio of sodium hydroxide to water is 1:75:110:12:3500. Solution A is slowly added dropwise to solution B, and stirring is continued for 5 hours to obtain a gel mixture; the gel mixture is transferred to a hydrothermal reactor with a polytetrafluoroethylene liner and crystallized under stirring. The crystallization temperature is 160°C and the crystallization time is 50 hours. After the crystallization is completed, the solid material is filtered. The solid is washed 8 times with distilled water, dried at 110°C for 10 hours, and then calcined at 550°C for 12 hours to obtain ZSM-23 molecular sieve A.
[0065] The specific surface area of ZSM-23 molecular sieve A is 234m 2 / g, pore volume 0.75cm 3 / g, and the most probable pore size is 0.55nm.
[0066] Figure 1 This is the wide angle X-ray diffraction (XRD) spectrum of ZSM-23 molecular sieve molecular sieve A. Figure 1 It is shown that the wide-angle x-ray diffraction angles of the sample are mainly: 2θ=7.9°, 8.2°, 11.4°, 19.7°, 21.1°, 23.0°, 24.0°, 24.2° and 24.8°. The above diffraction signals are consistent with the diffraction spectrum of ZSM-23 molecular sieve. This shows that the synthesized ZSM-23 molecular sieve A has a typical MTT framework structure.
[0067] (2) Preparation of two-dimensional hexagonal all-silica mesoporous molecular sieve raw powder
[0068] 120g of nonionic surfactant P123 was added to 3000g of 2M hydrochloric acid aqueous solution and stirred at 40℃ for 1h; 256g of ethyl orthosilicate was added to the above solution and stirred at 40℃ for 24h; the above mixture was transferred to a hydrothermal reactor and hydrothermally crystallized at 100℃ for 24h. After the hydrothermal reaction, the solid product was separated from the mother liquor, washed with deionized water until neutral, and dried at 110℃ for 5h to obtain the two-dimensional hexagonal all-silica mesoporous molecular sieve raw powder A.
[0069] (3) Preparation of microporous-mesoporous composite molecular sieves
[0070] 60g ZSM-23 molecular sieve A and 68g of the above-mentioned two-dimensional hexagonal all-silicon mesoporous molecular sieve raw powder A were mixed and put into a 300ml ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 2mm, the number was 5, and the rotation speed was 400r / min. The ball mill was closed and ball milled at 60°C for 12h to obtain a solid powder; the solid powder was dried at 110°C for 10h, and then calcined at 550°C for 16h to obtain a microporous-mesoporous composite molecular sieve A.
[0071] Based on the total weight of the microporous-mesoporous composite molecular sieve A, the content of the ZSM-23 molecular sieve A is 60% by weight, and the content of the two-dimensional hexagonal all-silicon mesoporous molecular sieve A is 40% by weight.
[0072] The specific surface area of microporous-mesoporous composite molecular sieve A is 367m 2 / g, pore volume 0.89cm 3 / g.
[0073] Figure 2 This is the small angle XRD spectrum of microporous-mesoporous composite molecular sieve A. Figure 2 The above shows that a strong diffraction signal appears between 2θ = 0.6°-1°, corresponding to the (110) crystal plane; two clear diffraction signals appear between 2θ = 1°-2°, indicating that the sample contains two-dimensional hexagonal mesoporous channels. In addition, the diffraction peak of the (110) crystal plane is high in intensity and narrow in shape, indicating that the mesoporous structure in the sample has good long-range order.
[0074] Figure 3 This is the pore size distribution diagram of microporous-mesoporous composite molecular sieve A. Figure 3 The above shows that the sample has an obvious double-pore structure, and the most probable pore sizes of the double pores are 0.55nm and 7.5nm respectively. Among them, the micropore channel with a pore size of 0.55nm is provided by the ZSM-23 molecular sieve, and the mesoporous channel with a pore size of 7.5nm is provided by the two-dimensional hexagonal all-silicon mesoporous molecular sieve.
[0075] (4) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins
[0076] The catalytic cracking performance of waste plastics of microporous-mesoporous composite molecular sieve A was evaluated in a fixed bed reactor. The loading amount of microporous-mesoporous composite molecular sieve A was 6 g, the loading amount of polyethylene waste plastic was 40 g, the reaction temperature was 520 ° C, the reaction pressure was 0.1 MPa, the reaction time was 2 hours, and the product was cooled and the gas-liquid separation was performed. The gas composition was measured by mixing with Al 2 O 3 -S capillary column and hydrogen flame detector (FID) Agilent 6890 gas chromatograph analysis, using programmed temperature, correction factor for quantitative analysis; liquid composition is analyzed by Agilent 6890 gas chromatograph equipped with PONA column. The reaction results are shown in Table 1.
[0077] Example 2
[0078] (1) Preparation of ZSM-23 molecular sieve
[0079] At room temperature, dimethylamine and aluminum sulfate were dissolved in distilled water and stirred for 24 hours to prepare a clear solution A; silica sol was mixed with an aqueous solution of sodium hydroxide to prepare a mixed solution B. 2 The molar ratio of sodium hydroxide to water is 1:65:100:10:3000. Solution A is slowly added dropwise to solution B, and stirring is continued for 5 hours to obtain a gel mixture; the gel mixture is transferred to a hydrothermal reactor with a polytetrafluoroethylene liner and crystallized under stirring. The crystallization temperature is 150°C and the crystallization time is 60 hours. After the crystallization is completed, the solid substance is filtered. The solid is washed with distilled water 5 times, dried at 80°C for 16 hours, and then calcined at 500°C for 20 hours to obtain ZSM-23 molecular sieve B.
[0080] The specific surface area of ZSM-23 molecular sieve B is 226m 2 / g, pore volume 0.73cm 3 / g, and the most probable pore diameter is 0.53nm.
[0081] (2) Preparation of two-dimensional hexagonal all-silica mesoporous molecular sieve raw powder
[0082] 153g of nonionic surfactant P123 was added to 2000g of 1M hydrochloric acid aqueous solution and stirred at 30℃ for 1h; 200g of methyl orthosilicate was added to the above solution and stirred at 30℃ for 30h; the above mixture was transferred to a hydrothermal reactor and hydrothermally crystallized at 110℃ for 20h. After the hydrothermal reaction, the solid product was separated from the mother liquor, washed with deionized water until neutral, and dried at 120℃ for 3h to obtain the two-dimensional hexagonal all-silica mesoporous molecular sieve raw powder B.
[0083] (3) Preparation of microporous-mesoporous composite molecular sieves
[0084] 55g ZSM-23 molecular sieve B and 69g of the above two-dimensional hexagonal all-silicon mesoporous molecular sieve B raw powder were mixed and put into a 300ml ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 2mm, the number was 4, and the rotation speed was 500r / min. The ball mill was closed and ball milled at 40°C for 24h to obtain a solid powder; the solid powder was dried at 70°C for 20h, and then calcined at 500°C for 20h to obtain a microporous-mesoporous composite molecular sieve B.
[0085] Based on the total weight of the microporous-mesoporous composite molecular sieve B, the content of the ZSM-23 molecular sieve B is 55% by weight, and the content of the two-dimensional hexagonal all-silicon mesoporous molecular sieve B is 45% by weight.
[0086] The specific surface area of microporous-mesoporous composite molecular sieve B is 380m 2 / g, pore volume 0.90cm 3 / g.
[0087] (4) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins
[0088] The reaction performance of the microporous-mesoporous composite molecular sieve B was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (4) of Example 1. The evaluation results are listed in Table 1.
[0089] Example 3
[0090] (1) Preparation of ZSM-23 molecular sieve
[0091] At room temperature, dimethylamine and aluminum sulfate were dissolved in distilled water and stirred for 24 hours to prepare a clear solution A; silica sol was mixed with an aqueous solution of sodium hydroxide to prepare a mixed solution B. 2 The molar ratio of sodium hydroxide to water is 1:85:120:14:4000. Solution A is slowly added dropwise to solution B, and stirring is continued for 5 hours to obtain a gel mixture; the gel mixture is transferred to a hydrothermal reactor with a polytetrafluoroethylene liner and crystallized under stirring. The crystallization temperature is 170°C and the crystallization time is 40 hours. After the crystallization is completed, the solid material is filtered. The solid is washed 10 times with distilled water, dried at 130°C for 5 hours, and then calcined at 600°C for 8 hours to obtain ZSM-23 molecular sieve C.
[0092] The specific surface area of ZSM-23 molecular sieve C is 238m 2 / g, pore volume 0.79cm 3 / g, and the most probable pore size is 0.57nm.
[0093] (2) Preparation of two-dimensional hexagonal all-silica mesoporous molecular sieve raw powder
[0094] 80g of nonionic surfactant P123 was added to 4000g of 1.5M hydrochloric acid aqueous solution, and stirred at 50℃ for 1h; 175g of water glass with a concentration of 28.26% was added to the above solution, and stirred at 50℃ for 18h; the above mixture was transferred to a hydrothermal kettle and hydrothermally crystallized at 90℃ for 30h. After the hydrothermal reaction, the solid product was separated from the mother liquor, washed with deionized water until neutral, and dried at 70℃ for 10h to obtain the two-dimensional hexagonal all-silica mesoporous molecular sieve raw powder C.
[0095] (3) Preparation of microporous-mesoporous composite molecular sieves
[0096] 65g ZSM-23 molecular sieve C and 52g of the above-mentioned two-dimensional hexagonal all-silicon mesoporous molecular sieve raw powder C were mixed and put into a 300ml ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 2mm, the number was 8, and the rotation speed was 300r / min. The ball mill was closed and ball milled at 80°C for 8h to obtain a solid powder; the solid powder was dried at 150°C for 3h, and then calcined at 600°C for 8h to obtain a microporous-mesoporous composite molecular sieve C.
[0097] Based on the total weight of the microporous-mesoporous composite molecular sieve C, the content of the ZSM-23 molecular sieve C is 65% by weight, and the content of the two-dimensional hexagonal all-silicon mesoporous molecular sieve C is 35% by weight.
[0098] The specific surface area of microporous-mesoporous composite molecular sieve C is 337m 2 / g, pore volume 0.86cm 3 / g.
[0099] (4) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins
[0100] The reaction performance of the microporous-mesoporous composite molecular sieve C was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (4) of Example 1. The evaluation results are listed in Table 1.
[0101] Example 4
[0102] (1) Preparation of ZSM-23 molecular sieve
[0103] At room temperature, dimethylamine and aluminum sulfate were dissolved in distilled water and stirred for 24 hours to prepare a clear solution A; silica sol was mixed with an aqueous solution of sodium hydroxide to prepare a mixed solution B. 2The molar ratio of sodium hydroxide to water is 1:75:90:12:3500. Solution A is slowly added dropwise to solution B, and stirring is continued for 5 hours to obtain a gel mixture; the gel mixture is transferred to a hydrothermal reactor with a polytetrafluoroethylene liner and crystallized under stirring. The crystallization temperature is 160°C and the crystallization time is 50 hours. After the crystallization is completed, the solid material is filtered. The solid is washed 8 times with distilled water, dried at 110°C for 10 hours, and then calcined at 550°C for 12 hours to obtain ZSM-23 molecular sieve D.
[0104] (2) Preparation of two-dimensional hexagonal all-silica mesoporous molecular sieve raw powder
[0105] According to the method of step (2) in Example 1, prepare two-dimensional hexagonal all-silica mesoporous molecular sieve raw powder A.
[0106] (3) Preparation of microporous-mesoporous composite molecular sieves
[0107] 50g ZSM-23 molecular sieve D and 85g of the above-mentioned two-dimensional hexagonal all-silicon mesoporous molecular sieve raw powder A were mixed and placed in a 300ml ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 2mm, the number was 5, and the rotation speed was 400r / min. The ball mill was closed and ball milled at a temperature of 60°C for 12h to obtain a solid powder; the solid powder was dried at 110°C for 10h, and then calcined at 550°C for 16h to obtain a microporous-mesoporous composite molecular sieve D.
[0108] Based on the total weight of the microporous-mesoporous composite molecular sieve D, the content of the ZSM-23 molecular sieve D is 50% by weight, and the content of the two-dimensional hexagonal all-silicon mesoporous molecular sieve A is 50% by weight.
[0109] The specific surface area of microporous-mesoporous composite molecular sieve D is 400m 2 / g, pore volume 0.93cm 3 / g.
[0110] (4) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins
[0111] The reaction performance of catalyst D was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (4) of Example 1. The evaluation results are listed in Table 1.
[0112] Example 5
[0113] (1) Preparation of ZSM-23 molecular sieve
[0114] At room temperature, dimethylamine and aluminum sulfate were dissolved in distilled water and stirred for 24 hours to prepare a clear solution A; silica sol was mixed with an aqueous solution of sodium hydroxide to prepare a mixed solution B. 2 The molar ratio of sodium hydroxide to water is 1:85:130:14:4000. Solution A is slowly added dropwise to solution B, and stirring is continued for 5 hours to obtain a gel mixture; the gel mixture is transferred to a hydrothermal reactor with a polytetrafluoroethylene liner and crystallized under stirring. The crystallization temperature is 170°C and the crystallization time is 40 hours. After the crystallization is completed, the solid material is filtered. The solid is washed 10 times with distilled water, dried at 130°C for 5 hours, and then calcined at 600°C for 8 hours to obtain ZSM-23 molecular sieve E.
[0115] (2) Preparation of two-dimensional hexagonal all-silica mesoporous molecular sieve raw powder
[0116] A two-dimensional hexagonal all-silica mesoporous molecular sieve C was prepared according to the method of step (2) in Example 3.
[0117] (3) Preparation of microporous-mesoporous composite molecular sieves
[0118] 70g ZSM-23 molecular sieve E and 45g of the above-mentioned two-dimensional hexagonal all-silicon mesoporous molecular sieve raw powder C were mixed and put into a 300ml ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 2mm, the number was 8, and the rotation speed was 300r / min. The ball mill was closed and ball milled at 80°C for 8h to obtain a solid powder; the solid powder was dried at 150°C for 3h, and then calcined at 600°C for 8h to obtain a microporous-mesoporous composite molecular sieve E.
[0119] Based on the total weight of the microporous-mesoporous composite molecular sieve E, the content of the ZSM-23 molecular sieve E is 70% by weight, and the content of the two-dimensional hexagonal all-silicon mesoporous molecular sieve C is 30% by weight.
[0120] The specific surface area of microporous-mesoporous composite molecular sieve E is 323m 2 / g, pore volume 0.85cm 3 / g.
[0121] (4) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins
[0122] The reaction performance of the microporous-mesoporous composite molecular sieve E was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (4) of Example 1. The evaluation results are listed in Table 1.
[0123] Example 6
[0124] (1) Preparation of ZSM-23 molecular sieve
[0125] ZSM-23 molecular sieve D was prepared according to the method of step (1) in Example 4.
[0126] (2) Preparation of two-dimensional hexagonal all-silica mesoporous molecular sieve raw powder
[0127] According to the method of step (2) in Example 1, prepare two-dimensional hexagonal all-silica mesoporous molecular sieve raw powder A.
[0128] (3) Preparation of microporous-mesoporous composite molecular sieves
[0129] 40g ZSM-23 molecular sieve D and 102g of the above-mentioned two-dimensional hexagonal all-silicon mesoporous molecular sieve raw powder A were mixed and placed in a 300ml ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 2mm, the number was 5, and the rotation speed was 400r / min. The ball mill was closed and ball milled at 60°C for 12h to obtain a solid powder; the solid powder was dried at 110°C for 10h, and then calcined at 550°C for 16h to obtain a microporous-mesoporous composite molecular sieve F.
[0130] Based on the total weight of the microporous-mesoporous composite molecular sieve F, the content of the ZSM-23 molecular sieve D is 40% by weight, and the content of the two-dimensional hexagonal all-silicon mesoporous molecular sieve A is 60% by weight.
[0131] The specific surface area of the microporous-mesoporous composite molecular sieve F is 434 m 2 / g, pore volume 0.96cm 3 / g.
[0132] (4) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins
[0133] The reaction performance of Catalyst F was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (4) of Example 1. The evaluation results are listed in Table 1.
[0134] Example 7
[0135] (1) Preparation of ZSM-23 molecular sieve
[0136] ZSM-23 molecular sieve E was prepared according to the method of step (1) in Example 5.
[0137] (2) Preparation of two-dimensional hexagonal all-silica mesoporous molecular sieve raw powder
[0138] A two-dimensional hexagonal all-silica mesoporous molecular sieve C was prepared according to the method of step (2) in Example 3.
[0139] (3) Preparation of microporous-mesoporous composite molecular sieves
[0140] 80g ZSM-23 molecular sieve E and 30g of the above-mentioned two-dimensional hexagonal all-silicon mesoporous molecular sieve raw powder C were mixed and put into a 300ml ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 2mm, the number was 8, and the rotation speed was 300r / min. The ball mill was closed and ball milled at 80°C for 8h to obtain a solid powder; the solid powder was dried at 150°C for 3h, and then calcined at 600°C for 8h to obtain a microporous-mesoporous composite molecular sieve G.
[0141] Based on the total weight of the microporous-mesoporous composite molecular sieve G, the content of the ZSM-23 molecular sieve E is 80% by weight, and the content of the two-dimensional hexagonal all-silicon mesoporous molecular sieve C is 20% by weight.
[0142] The specific surface area of the microporous-mesoporous composite molecular sieve G is 295m 2 / g, pore volume 0.83cm 3 / g.
[0143] (4) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins
[0144] The reaction performance of the microporous-mesoporous composite molecular sieve G was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (4) of Example 1. The evaluation results are listed in Table 1.
[0145] Comparative Example 1
[0146] (1) Preparation of ZSM-23 molecular sieve
[0147] ZSM-23 molecular sieve A was prepared according to the method of step (1) in Example 1.
[0148] (2) Preparation of two-dimensional hexagonal all-silica mesoporous molecular sieve raw powder
[0149] According to the method of step (2) in Example 1, prepare two-dimensional hexagonal all-silica mesoporous molecular sieve raw powder A.
[0150] (3) Preparation of microporous-mesoporous composite molecular sieves
[0151] 15g ZSM-23 molecular sieve A and 145g of the above-mentioned two-dimensional hexagonal all-silicon mesoporous molecular sieve raw powder A were mixed and placed in a 300ml ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 2mm, the number was 5, and the rotation speed was 400r / min. The ball mill was closed and ball milled at 60°C for 12h to obtain a solid powder; the solid powder was dried at 110°C for 10h, and then calcined at 550°C for 16h to obtain a microporous-mesoporous composite molecular sieve D1.
[0152] Based on the total weight of the microporous-mesoporous composite molecular sieve D1, the content of ZSM-23 molecular sieve A is 15% by weight, and the content of the two-dimensional hexagonal all-silicon mesoporous molecular sieve A is 85% by weight.
[0153] The specific surface area of the microporous-mesoporous composite molecular sieve D1 is 517 m 2 / g, pore volume 1.05cm 3 / g.
[0154] (4) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins
[0155] The reaction performance of the microporous-mesoporous composite molecular sieve D1 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (4) of Example 1. The evaluation results are listed in Table 1.
[0156] Comparative Example 2
[0157] (1) Preparation of ZSM-23 molecular sieve
[0158] ZSM-23 molecular sieve C was prepared according to the method of step (1) in Example 3.
[0159] (2) Preparation of two-dimensional hexagonal all-silica mesoporous molecular sieve raw powder
[0160] According to the method of step (2) in Example 3, prepare two-dimensional hexagonal all-silica mesoporous molecular sieve raw powder C.
[0161] (3) Preparation of microporous-mesoporous composite molecular sieves
[0162] 92g ZSM-23 molecular sieve C and 12g of the above-mentioned two-dimensional hexagonal all-silicon mesoporous molecular sieve raw powder C were mixed and put into a 300ml ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding balls were made of agate, the diameter of the grinding balls was 2mm, the number was 8, and the rotation speed was 300r / min. The ball mill was closed and ball milled at 80°C for 8h to obtain a solid powder; the solid powder was dried at 150°C for 3h, and then calcined at 600°C for 8h to obtain a microporous-mesoporous composite molecular sieve D2.
[0163] Based on the total weight of the microporous-mesoporous composite molecular sieve D2, the content of the ZSM-23 molecular sieve C is 92% by weight, and the content of the two-dimensional hexagonal all-silicon mesoporous molecular sieve C is 8% by weight.
[0164] The specific surface area of the microporous-mesoporous composite molecular sieve D2 is 261 m 2 / g, pore volume 0.79cm 3 / g.
[0165] (4) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins
[0166] The reaction performance of the microporous-mesoporous composite molecular sieve D2 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (4) of Example 1. The evaluation results are listed in Table 1.
[0167] Comparative Example 3
[0168] Cancel step (1) in Example 1.
[0169] A two-dimensional hexagonal all-silica mesoporous molecular sieve A was prepared according to the method of step (2) in Example 1.
[0170] According to step (3) in Example 1.
[0171] The reaction performance of the two-dimensional hexagonal all-silica mesoporous molecular sieve A was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (4) of Example 1. The evaluation results are listed in Table 1.
[0172] Comparative Example 4
[0173] ZSM-23 molecular sieve A was prepared according to the method of step (1) in Example 1.
[0174] Eliminate step (2) and step (3) in Example 1.
[0175] The reaction performance of ZSM-23 molecular sieve A was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (4) of Example 1. The evaluation results are listed in Table 1.
[0176] Comparative Example 5
[0177] (1) Preparation of ZSM-23 molecular sieve
[0178] ZSM-23 molecular sieve A was prepared according to the method of step (1) in Example 1.
[0179] (2) Preparation of two-dimensional hexagonal all-silica mesoporous molecular sieve raw powder
[0180] According to the method of step (2) in Example 1, prepare two-dimensional hexagonal all-silica mesoporous molecular sieve raw powder A.
[0181] (3) Preparation of microporous-mesoporous composite molecular sieves
[0182] 60 g of ZSM-23 molecular sieve A was mechanically mixed with 68 g of the above two-dimensional hexagonal all-silicon mesoporous molecular sieve raw powder A, and then calcined at 550° C. for 16 h to obtain a microporous-mesoporous composite molecular sieve D3.
[0183] (4) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins
[0184] The reaction performance of the microporous-mesoporous composite molecular sieve D3 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (4) of Example 1. The evaluation results are listed in Table 1.
[0185] Comparative Example 6
[0186] ZSM-23 molecular sieve A was prepared according to the method of step (1) in Example 1.
[0187] Eliminate step (2) in Example 1.
[0188] The microporous-mesoporous composite material D4 was prepared according to the method of step (3) in Example 1. The difference was that "40g of silicon dioxide powder (prepared in the laboratory, with a specific surface area of 274m 2 / g, pore volume 0.57cm 3 / g)” replaces “68g of the above-mentioned two-dimensional hexagonal all-silica mesoporous molecular sieve raw powder A”.
[0189] Based on the total weight of the microporous-mesoporous composite material D4, the content of the ZSM-23 molecular sieve is 60 weight %, and the content of the silicon dioxide is 40 weight %.
[0190] The reaction performance of the composite material D4 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (4) of Example 1. The evaluation results are listed in Table 1.
[0191] Comparative Example 7
[0192] Catalyst D5 was prepared in the same manner as in Example 1, except that the preparation of the two-dimensional hexagonal all-silicon mesoporous molecular sieve raw powder in step (2) was omitted, and in step (3), "68 g of the above-mentioned two-dimensional hexagonal all-silicon mesoporous molecular sieve raw powder A" was replaced with "40 g of all-silicon silicalite-1 zeolite molecular sieve carrier, and the specific surface area of the replaced carrier was 384 m 2 / g, pore volume is 0.29ml / g, and the most probable pore diameter is 0.55nm".
[0193] The reaction performance of catalyst D5 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (4) of Example 1. The evaluation results are listed in Table 1.
[0194] Table 1
[0195]
[0196]
[0197] It can be seen from the above results that the microporous-mesoporous composite molecular sieve provided by the present invention can directly catalyze the conversion of waste plastics into light olefins. The conversion rate of waste plastics is 100%, and the yield of light olefins is high.
[0198] In Comparative Example 1, the content of two-dimensional hexagonal all-silicon mesoporous molecular sieve is too high, and the content of ZSM-23 molecular sieve is too low. Due to the small number of acidic centers on the catalyst and insufficient activation sites during the reaction, the raw material conversion rate and the yield of light olefins are low.
[0199] In comparative example 2, the content of two-dimensional hexagonal all-silicon mesoporous molecular sieve is too low, and the content of ZSM-23 molecular sieve is too high. Due to the small number of mesoporous channels in the catalyst, the diffusion of reactants and product molecules is hindered during the reaction, resulting in a low yield of light olefins.
[0200] In Comparative Example 3, only two-dimensional hexagonal all-silicon mesoporous molecular sieve was used as the cracking catalyst, and no ZSM-23 molecular sieve was added. Since there were almost no active acidic centers on the catalyst, the raw material conversion rate and the yield of light olefins were low.
[0201] In Comparative Example 4, only ZSM-23 molecular sieve was used as the cracking catalyst, and no two-dimensional hexagonal all-silicon mesoporous molecular sieve was added. Since the catalyst did not contain mesoporous channels, the diffusion of reactant and product molecules was hindered during the reaction, resulting in a low yield of light olefins.
[0202] In Comparative Example 5, the ball milling process was eliminated in the preparation of the microporous-mesoporous composite molecular sieve, resulting in uneven dispersion of the mesoporous molecular sieve and the microporous molecular sieve in the microporous-mesoporous composite molecular sieve, affecting the diffusion effect and resulting in a lower yield of light olefins.
[0203] In Comparative Example 6, silica powder is used to replace the two-dimensional hexagonal all-silicon mesoporous molecular sieve. Due to the low specific surface area, small pore volume and irregular pore structure of silica, the dispersion effect is significantly lower than that of the two-dimensional hexagonal all-silicon mesoporous molecular sieve, resulting in a lower yield of low-carbon olefins in the prepared composite material.
[0204] In Comparative Example 7, all-silicon silicalite-1 zeolite molecular sieve is used to replace the two-dimensional hexagonal all-silicon mesoporous molecular sieve. Although the main skeleton components of the all-silicon silicalite-1 zeolite molecular sieve and the two-dimensional hexagonal all-silicon mesoporous molecular sieve are both silicon dioxide, the pores of the all-silicon silicalite-1 zeolite molecular sieve belong to the micropore category, which is not conducive to the diffusion of reactant and product molecules during the reaction process, resulting in a low yield of light olefins.
[0205] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A microporous-mesoporous composite molecular sieve, characterized in that: The microporous-mesoporous composite molecular sieve comprises a ZSM-23 molecular sieve and a two-dimensional hexagonal all-silicon mesoporous molecular sieve, wherein the specific surface area of the two-dimensional hexagonal all-silicon mesoporous molecular sieve is 500-800 m 2 / g, the pore volume is 0.8-1.5mL / g, and the average pore diameter is 6-9nm; and based on the total weight of the microporous-mesoporous composite molecular sieve, the content of the ZSM-23 molecular sieve is 40-80% by weight, and the content of the two-dimensional hexagonal all-silica mesoporous molecular sieve is 20-60% by weight.
2. The microporous-mesoporous composite molecular sieve according to claim 1, wherein: Based on the total weight of the microporous-mesoporous composite molecular sieve, the content of the ZSM-23 molecular sieve is 50-70% by weight, and the content of the two-dimensional hexagonal all-silicon mesoporous molecular sieve is 30-50% by weight; Preferably, based on the total weight of the microporous-mesoporous composite molecular sieve, the content of the ZSM-23 molecular sieve is 55-65% by weight, and the content of the two-dimensional hexagonal all-silicon mesoporous molecular sieve is 35-45% by weight.
3. The microporous-mesoporous composite molecular sieve according to claim 1 or 2, wherein: The specific surface area of the microporous-mesoporous composite molecular sieve is 290-440 m 2 / g, the pore volume is 0.8-1mL / g, the pore size distribution is bimodal, and the most probable pore sizes corresponding to the bimodal distribution are 0.4-0.7nm and 5-10nm respectively; Preferably, the specific surface area of the microporous-mesoporous composite molecular sieve is 320-400m 2 / g, the pore volume is 0.85-0.93mL / g, the pore size distribution is bimodal, and the most probable pore sizes corresponding to the bimodal distribution are 0.5-0.6nm and 6-9nm respectively; More preferably, the specific surface area of the microporous-mesoporous composite molecular sieve is 337-380 m 2 / g, the pore volume is 0.86-0.9mL / g, the pore size distribution is a bimodal distribution, and the most probable pore sizes corresponding to the bimodal distribution are 0.5-0.6nm and 7-8nm, respectively.
4. The microporous-mesoporous composite molecular sieve according to claim 1 or 2, wherein: The SiO2 / Al2O3 molar ratio of the ZSM-23 molecular sieve may be 90-130, preferably 100-120.
5. A method for preparing the microporous-mesoporous composite molecular sieve according to any one of claims 1 to 4, characterized in that: The preparation method comprises: (1) hydrolyzing a template, a silicon source and an acidic aqueous solution under hydrolysis gel-making conditions to obtain a gel mixture; crystallizing the gel mixture; and filtering and first drying the product obtained by the crystallization to obtain a mesoporous molecular sieve raw powder; (2) The mesoporous molecular sieve raw powder is mixed with ZSM-23 molecular sieve and subjected to ball milling treatment, and the solid powder obtained after ball milling is subjected to a second drying and calcining treatment to obtain a microporous-mesoporous composite molecular sieve.
6. The preparation method according to claim 5, wherein: In step (1), the template is a nonionic surfactant; the silicon source is an organic silicate or an inorganic silicon source; and / or, the molar concentration of the solute acid in the acidic aqueous solution is 0.5-3 mol / L; And / or, the molar ratio of the template, the silicon source, the acid in the acidic aqueous solution and the water in the acidic aqueous solution is 1:(40-100):(120-400):(6000-10000).
7. The preparation method according to claim 5, wherein: The conditions for hydrolysis and gelatin preparation include: temperature of 20-60°C and time of 12-36h; And / or, the crystallization conditions include: temperature of 70-150° C. and time of 8-72 h.
8. The preparation method according to claim 5, wherein: In step (2), the weight ratio of the mesoporous molecular sieve raw powder to the ZSM-23 molecular sieve is 1:(0.3-5); And / or, the calcination conditions include: temperature of 450-650° C., preferably 500-600° C.; time of 5-30 h, preferably 8-20 h.
9. Use of the microporous-mesoporous composite molecular sieve according to any one of claims 1 to 4 in the direct catalytic cracking of waste plastics to produce light olefins, wherein: The application comprises: contacting the waste plastic powder with a catalyst for reaction, wherein the catalyst is the microporous-mesoporous composite molecular sieve according to any one of claims 1 to 4.
10. The use according to claim 9, wherein: The contact conditions include: temperature of 420-580°C, pressure of 0.01-3MPa, and contact time of 0.5-12h; And / or, the weight ratio of the novel catalyst to the waste plastic powder is 1:(0.5-50).
Citation Information
Patent Citations
Catalyst compositions comprising small size molecular sieves crystals deposited on a porous material
CN105517708A
Catalytic cracking aid containing spherical composite mesoporous material, preparation method of catalytic cracking aid and application of catalytic cracking aid in catalytic cracking reaction of hydrocarbon oil
CN112892583A
Catalyst for preparing low-carbon olefin through catalytic cracking of waste plastics and preparation method of catalyst
CN113398982A
Catalyst for preparing propylene and preparation method and application of catalyst
CN113731477A
Catalytic materials and method for the preparation thereof
US20060182681A1